Prevalence of fissure sealants in a portuguese sample of adolescents - Veiga, Nélio (2015)
BACKGROUND The use of fissure sealants is an effective intervention for the primary prevention of pit and fissure caries in children and adolescents. The objective of this study was to determine the prevalence of fissure sealants in a portuguese sample of adolescents. PARTICIPANTS AND METHODS A sample of 293 adolescents aged 12 to 18 years old, attending a public school in Sátão, Portugal, was enrolled in this cross-sectional study. A self-administered questionnaire with questions about oral health behaviours, knowledge and socio-economic status was answered by the adolescents in the classroom. Clinical examination of oral health status and assessment of fissure sealants was accomplished by a trained and calibrated research team. The presence of fissure sealants in each tooth was assessed as total or partial. Prevalence was expressed in proportions and compared by the chi-square test. Crude odds ratio (OR) with 95% confidence intervals (CI) were used to measure the strength of association between the presence of fissure sealants and the independent variables. RESULTS We verified that 26.3% (95%CI= 25.0-34.0) of adolescents refer knowing the definition of a fissure sealant, while only 5.9% (95%CI= 4.3-7.0) refer having fissure sealants applied on their teeth. The prevalence of fissure sealants was 52.7% (95%CI= 35.0-46.0), higher among the female gender (59.6% vs 46.2%, p=0.03). The presence of fissure sealants was associated with a lower prevalence of dental caries (dental caries, OR=0.32, 95%CI=0.18-0.59) and residence area (rural, OR=2.24, 95%CI=1.25-4.02). Among the adolescents with at least one tooth with fissure sealants, 21.7% (95%CI=13.9-30.0) presented total fissure sealants in sealed teeth, while 78.3% (95%CI= 70.1-86.1) presented one or more teeth with partial fissure sealant. CONCLUSIONS We found a low prevalence of fissure sealants and a high prevalence of partial and infiltrated sealants among adolescents. A low prevalence of adolescents know the definition and indications of a fissure sealant. It is necessary the establishment of a more targeted preventive program with better and more effective oral health education.